Improving Gross Motor Skill By Traditional Games - Bendriyanti, Rita Prima; Haryono, Mimpira (Journal of Education Technology, 2021)
The child's gross motoric development has not yet been developed. The child has not been able to coordinate body movements to train flexibility, balance, and agility, has not been able to coordinate the movements of the eyes, feet, hands, head in imitation, has not been able to do physical games with rules. This study aimed to analyze the traditional game of jumping rope to increase gross motor capacity in early childhood. This type of research is classroom action research. This study uses the Jjpn Elliot model in each cycle, and there are four main activities: planning, action, observation, and reflection. The subjects of this study were 15 students. Data collection techniques used in this study are observation and documentation. The instrument used in this research is a questionnaire. The data analysis used in this research is descriptive qualitative-quantitative. The result of the research is that the percentage of the implementation of the action in the first cycle is 75% (developing as expected), and a significant increase is shown in the second cycle with a percentage of 86% (developing very well). It can be concluded that children's gross motor skills can be increased by using the traditional game of jumping rope. This research implies that teachers can use the traditional jumping rope game to improve gross motor skills in early childhood.